Findings of Gynecomastia That Developed in Follow-up Secondary to Bicalutamide Treatment on Bone Scan - Unal, Kemal; Gokcora, Nahide (GALENOS YAYINCILIK, 2020)
Prostate cancer is a common neoplastic disease especially in elder patients. Metastatic prostate disease has low five-year survival rate. Bicalutamide is an androgen receptor antagonist that acts as an inhibitor by competizing androgen receptors in the target tissue and used as a treatment option in prostate cancer. Bone scan was performed on a 79-year-old male with prostate cancer in our department. Blood pool images showed bilateral hyperemia in the breast regions which was not present on the previous scan one year ago. On physical examination, there was bilateral painful gynecomastia. It was learned that the patient was given Bicalutamide therapy after the first bone scan. Blood pool images may detect this side effect and should be evaluated with physical examination in case of clinical doubt.
Keywords: Bicalutamide; gynecomastia; bone scan; prostate cancer